Minimum Wages in Sub-Saharan Africa : A Primer - Bhorat, Haroon (Published by Oxford University Press on behalf of the World Bank, 2018)
The fraction of workers currently covered by minimum wages in Sub-Saharan Africa (SSA) is small, but as formality and urbanization increase, wage regulation will become increasingly relevant. In this analysis, we find that higher minimum wage values are associated with higher levels of GDP per capita, in both SSA and non-SSA countries. Using two measures to assess the level at which minimum wages are set, we find that minimum wages in SSA countries are on average lower—relative to average wages—than most other comparable regions of the world. Thus, SSA as a whole reflects no particular bias toward a comparatively more pro–minimum wage policy. Within SSA, however, we observe that low-income countries set relatively higher minimum wages than middle- or upper-income countries. We find significant variation in the detail of minimum wage regimes and schedules in the region, as well as large variations in compliance. Notably, several countries in SSA have relatively complex minimum wage schedules, and on average we find high levels of noncompliance among covered workers. We also summarize the limited research on the employment effects of minimum wages in SSA, which are consistent with global results. By and large, introducing and raising the minimum wage appears to have small negative employment impacts or no statistically significant negative impacts. There are country studies, however, where substantial negative effects on employment are reported—often for specific cohorts. The release of country-level earnings and employment data at regular intervals lies at the heart of a more substantive, country-focused minimum wage research agenda for Africa.